PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. SAWIT KALTIM LESTARI SABINTULUNG MUARA KAMAN - Juraidi; Eva Noorhya Akhmar Ramadhan Putri; Muhammad Zainuddin (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2024)
The achievement of improving an employee's performance can be seen from each completion of work carried out. If an employee is able to complete all assigned tasks well, accompanied by a good attitude, such as a good level of absenteeism, then the employee is considered to have maximum performance. In the last three years, PT. Sawit Kaltim Lestari declined but production realization remained almost perfect. There are many factors that can influence employee performance, especially for employees who work in the production department. One of them is the guarantee of Occupational Safety and Health (K3) levels provided by the company to employees, a supportive work environment, and employee motivation. The aim of this research is to determine the influence of Occupational Safety and Health (K3), Work Environment and Motivation. The sample in this study was 66 respondents. The data was then analyzed using the multiple regression method. The results of the research show that Occupational Health and Safety (K) has a partial positive and significant effect, the work environment has a partial positive and significant effect, motivation has a partial positive and significant effect, and Occupational Health and Safety, Work Environment, and Motivation have a positive and significant effect simultaneously on the performance of PT. Sawit Kaltim Lestari.